Chlamydia Trachomatis and Human Papillomavirus Serostatus in Puerto Rican Women - Castañeda-Avila, Maira A.; Suárez-Pérez, Erick; Bernabe-Dones, Raúl; Unger, Elizabeth R.; Panicker, Gitika; Ortiz, Ana P. (Puerto Rico Health Sciences Journal, 2020)
Objective: There is a high prevalence of human papillomavirus (HPV) infection in Puerto Rico, but little is known about the prevalence of Chlamydia trachomatis (CT) infection in healthy Puerto Rican women. Thus we aimed to evaluate the seroprevalence and association and the association between HPV and CT. Methods: This was a secondary data analysis from a cross-sectional, populationbased, study of HPV infection in women aged 16-64 years in Puerto Rico (2010-2013). Enzyme-linked immunosorbent assays (ELISA) were used to detect serum antibodies to CT and HPV. Logistic regression models were used to estimate the odds ratio (OR) for the association between HPV and CT serostatus. Results: The study included 524 women; mean age was 42 years. Overall, 97 (18.5%) women were CT-seropositive, 251 (47.0%) were HPV seropositive, and 57 (10.9%) had antibodies for both CT and HPV. Women who were CT-seropositive were more likely (p<0.05) to also be seropositive to any HPV type (ORadjusted: 1.7, IC 95% =1.1, 2.6), HPV 16/18 (ORadjusted: 1.6, IC 95% =1.0, 2.6) and HPV 6/11 (ORadjusted: 1.6, IC 95% =1.1, 2.6) than those CT-seronegative, after adjusting for possible confounding factors. Conclusion: Given the association between CT and HPV seropositivity, longitudinal studies to evaluate whether CT infection influences HPV incidence and persistence in this group are warranted.